2013
DOI: 10.1001/jamadermatol.2013.1609
|View full text |Cite
|
Sign up to set email alerts
|

CD200 Upregulation in Vascular Endothelium Surrounding Cutaneous Squamous Cell Carcinoma

Abstract: CD200 expression on local blood vessels may promote tumor progression by suppressing CD200R myeloid cells during diapedesis. These data highlight a previously unrecognized mechanism of immune evasion by SCC and may provide guidance for the development of targeted therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…Th2 cells and macrophages as well as melanocytes produce IL-24 (Poindexter et al , 2005), and those cells reside in the SCC microenvironment. In fact, IL-24 mRNA was also up-regulated in inflammatory infiltrating cell regions surrounding tumor nests compared to normal reticular dermis (Belkin et al , 2013). We thus concluded that IL-24 can be derived from multiple cell types including cancer cells within the SCC microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Th2 cells and macrophages as well as melanocytes produce IL-24 (Poindexter et al , 2005), and those cells reside in the SCC microenvironment. In fact, IL-24 mRNA was also up-regulated in inflammatory infiltrating cell regions surrounding tumor nests compared to normal reticular dermis (Belkin et al , 2013). We thus concluded that IL-24 can be derived from multiple cell types including cancer cells within the SCC microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…CD200 gene and message were upregulated in SCC stroma (Belkin et al, 2013). E2F1 and E2F7 were both found overexpressed in cSCCs compared with normal epidermis (Belkin et al, 2013). With detection by quantitative real-time reverse transcriptase polymerase chain reaction, DGCR8, AGO1, AGO2, PACT, and TARBP1 expression levels were found significantly higher in the SCC than the healthy controls .…”
Section: Abnormally Expressed Genes In Csccmentioning
confidence: 90%
“…While the normal epidermis showed a negative to weak-positive expression of MUC4, its expression was significantly upregulated in SCCs where the intensity of staining correlated negatively with tumour grade and positively with age (Chakraborty et al, 2010). CD200 gene and message were upregulated in SCC stroma (Belkin et al, 2013). E2F1 and E2F7 were both found overexpressed in cSCCs compared with normal epidermis (Belkin et al, 2013).…”
Section: Abnormally Expressed Genes In Csccmentioning
confidence: 95%
“…HDBECs (PromoCell, Heidelberg, Germany) were cultured as previously described [27]. HDBECs were transfected using PromoFectin-HUVEC according to manufactures recommendations.…”
Section: Methodsmentioning
confidence: 99%